An integrated photoanode based on non-critical raw materials for robust solar water splitting. Issue 5 (13th July 2020) - Cardenas-Morcoso, Drialys; García-Tecedor, Miguel; Merdzhanova, Tsvetelina; Smirnov, Vladimir; Finger, Friedhelm; Kaiser, Bernhard; Jaegermann, Wolfram; Gimenez, Sixto
Abstract : An integrated photovoltaic–electrocatalytic device with a novel design is presented, achieving 7.7.% STH efficiency for unassisted solar water splitting. Abstract : Herein, we have developed an integrated photoanode for solar water splitting based on an "Earth-abundant" Ni–Fe based electrocatalyst combined with a versatile multijunction Si-based photovoltaic device, designed in such a way to allow a direct coupling with the electrocatalyst with minimal losses. The water oxidation catalyst was prepared by electrochemical deposition of iron on a nickel foil, followed by thermal annealing, leading to the formation of NiO, α-Fe2 O3, and NiFe2 O4 phases. Detailed structural and surface characterization revealed the effect of the addition of different Fe contents and the subsequent implications on the electrocatalytic performance. The optimized integrated photoanode delivered a maximum photocurrent density of 6.2 mA cm −2 at 0 V applied bias, which corresponds to a 7.7% of Solar-To-Hydrogen conversion efficiency, which remained stable for more than 20 hours. These results pave the way towards large-scale, efficient and low-cost solar energy conversion solutions based on non-critical raw materials.